PENETAPAN KADAR KAFEIN DAUN Camellia sinensis SECARA EKSTRAKSI PELARUT - Sry Hardiyanti, Andi; Muhammad Ashar Muslimin; Erna Erawaty (Nusantara Hasana Journal, 2025)
Tea is a medicinal plant with many benefits. These include as an anticancer, antioxidant, antimicrobial, antibacterial, and prevention of osteorosclerosis. The Camellia sinensis plant produces tea from its leaves and shoots. Caffeine is one of the ingredients in tea plants. The purpose of this study was to determine the caffeine content of Camellia sinensis. The research method uses ether for the sample socletation process, then heated. Furthermore, methyl red indicator to identify caffeine then titrated with 0.2 N NaOH and weighed the caffeine content % (b/b). The results obtained from the socletation process of 10 grams of Camellia sinensis leaves are 400 mL. The addition of methyl red indicator produced a pink color change indicating that the sample was positive for caffeine. Determination of caffeine content using the titration method with NaOH 0.2 N solution as much as 71 mL produces a clear color change. In the calculation of the percent of caffeine content is 2.27%. The conclusion from the data is that there is caffeine content in green tea in accordance with the requirements for the value of content in tea leaves 0.5%-4%, so that the results of the study show that it is in accordance with the literature and the Indonesian herbal pharmacopoeia.